Diary of a Wimpy Kid : The Getaway - Kinney, Jeff (UK Puffin Books, 2017)
Greg Heffley and his family escape to a tropical island resort for some much-needed rest and relaxation, but sun poisoning, stomach troubles, and venemous creatures all threaten their vacation
Include Illustration
Keywords: Resorts -- Juvenile fiction -- Family vacations -- Juvenile fiction -- Heffley, Greg -- Juvenile fiction